KAJIAN HUKUM DAN SOSIAL BUDAYA TERHADAP ANAK TERLANTAR BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Feibe Engeline Pijoh; Joupy G.Z. Mambu; Jeflan Recky Lalensang (Labor Program Studi Pendidikan Sosiologi, 2022)
The aim of the research is to find out the causes of child neglect and to find out the protection of Law Number 35 of 2014 against the problems of abandoned children in Indonesia. The research method is normative legal research or library law research. This is done by examining literature or legal materials that contain normative rules. The results of the study show that legal protection is a mandatory thing that must be done by parents, families, communities, government and the state in protecting and protecting children so they do not become neglected children. The form of legal protection that must be given to abandoned children is that parents have an obligation to maintain and protect children's rights